The co-factor of LIM domains (CLIM/LDB/NLI) maintains basal mammary epithelial stem cells and promotes breast tumorigenesis. - Michael L Salmans; Zhengquan Yu; Kazuhide Watanabe; Eric Cam; Peng Sun; Padhraic Smyth; Xing Dai; Bogi Andersen (PLoS Genetics, 2014)
Mammary gland branching morphogenesis and ductal homeostasis relies on mammary stem cell function for the maintenance of basal and luminal cell compartments. The mechanisms of transcriptional regulation of the basal cell compartment are currently unknown. We explored these mechanisms in the basal cell compartment and identified the Co-factor of LIM domains (CLIM/LDB/NLI) as a transcriptional regulator that maintains these cells. Clims act within the basal cell compartment to promote branching morphogenesis by maintaining the number and proliferative potential of basal mammary epithelial stem cells. Clim2, in a complex with LMO4, supports mammary stem cells by directly targeting the Fgfr2 promoter in basal cells to increase its expression. Strikingly, Clims also coordinate basal-specific transcriptional programs to preserve luminal cell identity. These basal-derived cues inhibit epidermis-like differentiation of the luminal cell compartment and enhance the expression of luminal cell-specific oncogenes ErbB2 and ErbB3. Consistently, basal-expressed Clims promote the initiation and progression of breast cancer in the MMTV-PyMT tumor model, and the Clim-regulated branching morphogenesis gene network is a prognostic indicator of poor breast cancer outcome in humans.